Mechanical tricuspid valve thrombosis in pregnancy: a case report and literature review on anticoagulation challenges and fetal protection strategies - Zhu, San; Luo, Can; Luo, Bing; Zhang, Yaoyao; Wei, Qiang (Frontiers in Pediatrics, 2025)
BackgroundPregnancy in women with mechanical heart valves (MHVs) poses significant challenges in balancing maternal thromboprophylaxis and fetal safety. Anticoagulation strategies must simultaneously prevent life-threatening valve thrombosis and minimize fetal risks, yet optimal management remains controversial. While warfarin offers effective thromboprophylaxis, its embryotoxicity at higher doses (>5 mg/day) contrasts with low molecular weight heparin (LMWH), which lacks consensus on thrombotic efficacy despite fetal safety advantages.Case presentationWe report a case of a 30-year-old woman with mechanical mitral and tricuspid valves. She was maintained on low-dose warfarin (target INR 2.5–3.0) during early pregnancy. At 26–28 weeks of gestation, she developed exertional dyspnea; initial imaging showed stable valve function. At 33 + 2 weeks, worsening symptoms and echocardiographic evidence of tricuspid valve dysfunction prompted anticoagulation transition from warfarin to LMWH combined with vitamin K. After achieving an INR <1.4, cesarean delivery was performed at 33 + 3 weeks under general anesthesia, resulting in a live male infant without cardiac anomalies. Three days postpartum, mechanical tricuspid valve thrombosis with severe regurgitation was confirmed, necessitating bioprosthetic valve replacement on postoperative day 4. Maternal and neonatal outcomes were favorable.ConclusionsThis case highlights the importance of individualized anticoagulation management, multidisciplinary coordination, and vigilant monitoring in optimizing outcomes for pregnant patients with MHVs. Tailored pharmacologic strategies represent key modifiable prenatal factors influencing both maternal safety and child health.